PERILAKU PENYIMPANGAN SEKSUAL SUAMI TERHADAP ISTRI DALAM IKATAN PERKAWINAN - Taufik; Nailah Mumtazah (Sahaja: Journal Sharia and Humanities, 2024)
This study discusses the problem of sexual deviation behavior in marital relations and analyzes the Judge's Decision at the West Jakarta Religious Court. This study aims to determine the forms of sexual deviant behavior as well as Islamic legal remedies that must be carried out on sexual deviant behavior and analyze the judge's decision to settle divorce cases due to sexual deviant behavior. This study uses a qualitative research method of library research. The primary data source in this study is the Judge's Decision Document at the West Jakarta Religious Court while the secondary data sources are in books, journals, newspapers and previous research. The result of this study is that the sexual deviation of a husband against his wife according to Article 8 letter A of Law Number 23 of 2004 is an act of violence which is defined as any act in the form of forcing sexual intercourse, forcing sexual relations in an unnatural way to be liked by the wife.